Influence of a hydrophobic resin coating on the immediate and 6-month dentin bonding of three universal adhesives. Issue 10 (October 2015) - Sezinando, Ana; Luque-Martinez, Issis; Muñoz, Miguel Angel; Reis, Alessandra; Loguercio, Alessandro D.; Perdigão, Jorge
Highlights The objective was to study the influence of a hydrophobic resin coating on the 6-month microtensile dentin bond strengths (μTBS) and nanoleakage (NL) of three universal adhesives applied in self-etch or in etch-and-rinse mode. The universal adhesives Scotchbond Universal Adhesive (3M ESPE); All-Bond Universal (Bisco Inc.); and G-Bond Plus or G-ænial Bond (GC Co.) were applied under etch-and-rinse or self-etch modes. The use of a "hydrophobic resin coating" (with or without Heliobond, Ivoclar Vivadent), and "storage time" (24h or 6m) were the other factors. The application of a hydrophobic resin coating improved the 6m performance of all three universal adhesives when applied in SE mode.